DYNAMICS OF EXCHANGE RATE OF RUR AND USD AS AN INDICATOR OF ECONOMIC DEVELOPMENT - Irina P. Kurochkina; Olga V. Pisareva (Статистика и экономика)
The article focuses on key trends in the foreign exchange market and the indicators that affect the fluctuations in the exchange rate of the Russian ruble and the U.S. dollar. There is a multivariate regression model designed to assess the effect of factors on the behavior of the exchange rate of the ruble.